2010
DOI: 10.1063/1.3476357
|View full text |Cite
|
Sign up to set email alerts
|

Surface-plasmon enhancement of band gap emission from ZnCdO thin films by gold particles

Abstract: We present our study of the dependence of surface plasmon (SP) coupled band gap emission and defect emission on the sputtering time of gold particles on ZnCdO films. Eightfold enhancement of the band gap emission from ZnCdO thin films coated with Au particles is observed, while the defect emission is completely suppressed. The remarkable enhancement of the band gap emission is mainly attributed to the coupling between excitons in ZnCdO films and the SP of Au particles. While the suppression of the defect emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…While for the sample ZnCdO on Au/Si substrate, the τ 1 = 29 ± 10 ps and τ 2 = 240 ± 45 ps. These time constants are comparable to those of ZnCdO reported earlier by Yang et al [47]. An initial fast decay component τ 1 =τ NR is attributed to the capture of excitons and trapping of carriers by deep centers of defects and impurities (centers of the non-radiative recombination) and process of the multiphonon emission [48].…”
Section: Al 2 O 3 and (C) Sisupporting
confidence: 69%
See 1 more Smart Citation
“…While for the sample ZnCdO on Au/Si substrate, the τ 1 = 29 ± 10 ps and τ 2 = 240 ± 45 ps. These time constants are comparable to those of ZnCdO reported earlier by Yang et al [47]. An initial fast decay component τ 1 =τ NR is attributed to the capture of excitons and trapping of carriers by deep centers of defects and impurities (centers of the non-radiative recombination) and process of the multiphonon emission [48].…”
Section: Al 2 O 3 and (C) Sisupporting
confidence: 69%
“…Yang et al has reported that that the Au particles can greatly reduce the nonradiative recombination rate by passivation of surface states and make the decay time slow down [47]. Additionally, we can find the internal quantum efficiency of ZnCdO η int (ZnCdО), which can be described as: [47]. Calculated parameters are shown in the Table 3.…”
Section: Al 2 O 3 and (C) Simentioning
confidence: 97%
“…PL integrated intensities at 10 K were normalized to 1. The inset is the schematic diagram for the emission from GaN LEDs (η extraction ) by the following relation: η ext = η int × η extraction [21]. The η int of LED was estimated by comparing PL intensities assuming that the η int is 100 % at 10 K regardless of excitation carrier density [22].…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13] However, fabrication of ZnCdO films and heterostrctures by pulsed laser deposition (PLD) is rarely reported. 5,[14][15][16][17] Recent works on the optical properties of GaN-based QWs have shown that localized exciton transitions always dominate in this system at low temperatures 18,19 and the degree of carrier localization is strongly correlated with the composition concentrations, well width, and interface roughness. 20,21 The understanding of carrier dynamics is essential for the lasing application.…”
Section: Introductionmentioning
confidence: 99%